Does the Scale or Speed of Immigration Generate Nativism? Evidence from a Comparison of New Zealand Regions. (March 2022) - Wilson, Chris; Shastri, Sanjal; Frear, Henry
Nativism, the belief that the rights of those who came first should be prioritized over immigrants, is an increasingly important driver of the rise of far-right populism. It is also leading to hate crimes and even terrorist attacks against immigrants. However, it remains unclear when and why local communities come to oppose immigration. One important set of questions concerns whether nativism is most likely to emerge in societies in which immigrants constitute a higher proportion of the total population or those where there is rapid growth in the immigrant population, even if absolute numbers or their proportion of society remain low. This paper employs multivariate analysis to test these two hypotheses. We use data from a survey of nativist (and populist) sentiment in New Zealand conducted in 2020 along with population data from the national censuses of 2013 and 2018. We compare the results from all New Zealand regions. Our findings strongly support the second hypothesis regarding the importance of the rate of growth in the immigrant population. Those regions that have the highest rate of change in immigrant populations present the highest levels of nativist sentiment, despite their immigrant populations being both small in size and as a proportion of the local population. Conversely, those regions where immigrant numbers are high or they constitute a large proportion of the local population return low levels of nativist sentiment.